Hello, we have just begun using the chain rule in Calculus 1, but I am stumped on a problem which is blinding me to everything else.
It seems like it should be simple, but I just cannot get it worked out properly!
Given: y=f(x) with f(1)=4 and f'(1)=3, find:
- (a.) g'(1) if g(x)=sq. rt. of f(x)
+ (a.) g'(1) if g(x)=sq. rt. of f(x)....which works out to g'(1)=3/4
but I cannot figure out:
(b.) h'(1) if h(x)=f(sq.rt. of x)
Please, if someone could please offer me assistance, even some hints would be appreciated.
These are driving me insane with frustration and I have a 105% average in my class!!! What am I overlooking????